Short-term gain for long-term pain? Which patients should be treated and should we ration?. (March 2013) - Lane, T R A; Dharmarajah, B; Kelleher, D; Franklin, I J; Davies, A H
Objectives: Treatments of common conditions which do not affect mortality often become sidelined in the drive to improve efficiency and reduce costs. The rationing of patients is a divisive but crucial component to universal health care. How should this be accomplished? Methods and Results: In this article we examine the outcomes of various rationing methods in varicose veins. Conclusions: No method is perfect and treatment of symptoms and complications should remain the target for all physicians.